PENGARUH KOMUNIKASI INFLUENCER PADA MEDIA SOSIAL DALAM MENINGKATKAN PENJUALAN - Yunimar .; Cecep Safa'atul Barkah; Lina Auliana; Iwan Sukoco (Jurusan Ilmu Komunikasi Universitas Andalas, 2022)
In increasing marketing on social media, companies or brands have started to use the services of influencers as a strategy to promote their products or services. Influencers are used by a brand to provide information about the brand to its followers. The purpose of this study is to find out how influencers convey information about a product or service so that followers are interested in trying it so that they can increase sales. The research method used is to use a literature review approach and make observations on one of the influencers in Indonesia. With the influencer, the brand awareness of a product will increase which will affect sales.